2023
DOI: 10.3390/jmse11061115
|View full text |Cite|
|
Sign up to set email alerts
|

Behavioural Responses to Ultrasound Antifouling Systems by Adult Solitary Ascidians

Abstract: Ultrasonic antifouling devices are installed globally on a variety of vessel types and are marketed as an environmentally friendly method for biofouling control. The aim of this study was to examine the effects of ultrasound on adults of three species of common solitary ascidians (Ciona intestinalis, Ascidiella aspersa and Styela plicata). After a brief (10 s) exposure to two ultrasound frequencies (30 and 35 kHz), alterations in the frequency of siphon closing events and the length of time the siphons remaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…These experiments revealed that the coronal organ plays a role in perceiving ultrasounds, exhibiting a frequency-dependent behavioral response. Higher sensitivity was observed at the highest frequency tested ( Varello et al, 2023 ).…”
Section: Mechanosensation In Adult Tunicatesmentioning
confidence: 88%
“…These experiments revealed that the coronal organ plays a role in perceiving ultrasounds, exhibiting a frequency-dependent behavioral response. Higher sensitivity was observed at the highest frequency tested ( Varello et al, 2023 ).…”
Section: Mechanosensation In Adult Tunicatesmentioning
confidence: 88%
“…In the original publication [1], Trickey et al, 2022 was not cited. The citation has now been inserted in the first sentence of Section 5, and should read as follows:…”
Section: Missing Citationmentioning
confidence: 99%